Access and benefit sharing toolkit for the management of genetic resources and associated traditional knowledge in Bhutan: (Acc: D 1848) - National Biodiversity Centre (MOAF) (Thimphu: National Biodiversity Centre (MOAF), 2018)
Includes references.
Keywords: Environment